Lateral flow assay: a promising rapid point-of-care testing tool for infections and non-communicable diseases - Vealan, Kumaravel; Joseph, Narcisse; Alimat, Sharizah; Karumbati, Anandi S.; Thilakavathy, Karuppiah (Sciendo, 2023)
The point-of-care testing (POCT) approach has established itself as having remarkable importance in diagnosing various infectious and non-communicable diseases (NCDs). The POCT approach has succeeded in meeting the current demand for having diagnostic strategies that can provide fast, sensitive, and highly accurate test results without involving complicated procedures. This has been accomplished by introducing rapid bioanalytical tools or biosensors such as lateral flow assays (LFAs). The production cost of these tools is very low, allowing developing countries with limited resources to utilize them or produce them on their own. Thus, their use has grown in various fields in recent years. More importantly, LFAs have created the possibility for a new era of incorporating nanotechnology in disease diagnosis and have already attained significant commercial success worldwide, making POCT an essential approach not just for now but also for the future. In this review, we have provided an overview of POCT and its evolution into the most promising rapid diagnostic approach. We also elaborate on LFAs with a special focus on nucleic acid LFAs.